Gasteroid fungi – the morphological characteristics of selected endangered and rare species noted in Poland - Łuszczyński, Janusz; Tomaszewska, Agnieszka (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2014)
The aim of the work was to present the characteristics of selected species from Disciseda, Geastrum and Tulostoma genera which due to the small differences in morphology of their fruit bodies may pose some identification problems. The selected species of gasteroid fungi of these genera are described based on the materials collected during the course of our studies. All materials were gathered during the research into macromycetes in xerothermic habitats located in the Nida Basin. Taxa noted by us are considered to be very rare in the mycobiota of Poland and are highly endangered.